Design of Image Processing System Based on Charge Coupled Device - Xu Guosheng; Wang Yumei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To speed up the image acquisition and make full use of effective information, a design method of CCD partial image scanning system is presented. The system achieves to functions of the high -speed data collection, the high -speed video data compression the real time video data Network Transmission and the real time compression picture data storage. the data processed was transferred to PC through USB2.0 real-time to reconstruct defects microscopic images. The experimental results demonstrated that defects within 50μm～1000μm were inspected effectively by the CCD scanning defects inspection instrument, that this method has a repetition error no more than 2.24 pixels, with high precision and good anti-noise ability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2194